Do coup leaders matter? Leadership change and economic growth in politically unstable countries - Richard Jong-A-Pin; Shu Yu (ETH Zurich, KOF Swiss Economic Institute, 2010)
We examine the impact of leadership change after a coup d'etat on economic growth. We consider successful coup attempts as our treatment group and use failed coup attempts as controls to condition on political instability. To take account of selection bias, we control for the determinants of coup success. Our main finding is that leadership changes after a coup d'état have a positive effect on economic growth in the least developed countries, but have a negative effect in other developing countries.
Keywords: 330; economic growth; coup d'etat; political instability; Wirtschaftswachstum; Diktatur; Politische Unruhen; Entwicklungsländer; Welt